Diets rich in whole grains increase betainized compounds associated with glucose metabolism. Issue 5 (25th September 2018) - Kärkkäinen, Olli; Lankinen, Maria A; Vitale, Marilena; Jokkala, Jenna; Leppänen, Jukka; Koistinen, Ville; Lehtonen, Marko; Giacco, Rosalba; Rosa-Sibakov, Natalia; Micard, Valérie; Rivellese, Angela A A; Schwab, Ursula; et al.
ABSTRACT: Background: Epidemiologic evidence suggests that diets rich in whole grains are associated with a reduced risk of developing chronic diseases and all-cause mortality. However, the molecular mechanisms behind these beneficial metabolic effects are poorly understood. Objective: Our aim was to investigate novel trimethylated (betainized) compounds from mice and humans, and their association with whole grain–rich diets and insulin resistance and insulin secretion. Design: Fasting plasma samples were obtained in a mouse (C57BL/6J male) feeding trial and a controlled dietary intervention. The mouse trial involved feeding the mice a rye and wheat bran–enriched feed which was compared with a high-fat diet. In the human trial, participants recruited from Kuopio, Finland ( n  = 69) and Naples, Italy ( n  = 54) with characteristics of the metabolic syndrome were randomly assigned to either a whole grain–enriched diet or a control diet for 12 wk. Plasma concentrations of betainized compounds were analyzed with the use of liquid chromatography-tandem mass spectrometry. Insulin resistance and insulin secretion were assessed in an oral-glucose-tolerance test and a meal-glucose-tolerance test. Results: The betaines that were increased in mouse plasma after bran-enriched feeding were identified de novo via chemical synthesis and liquid chromatography-tandem mass spectrometry, and confirmed to be associated with an increased intake of whole-grain products in humans. In particular, the concentrations of pipecolic acid betaine were increased at the end of the whole-grain intervention in both the Kuopio cohort ( P  < 0.001) and the Naples cohort ( P  < 0.05), and these concentrations inversely correlated with the postprandial glucose concentration. Furthermore, the concentration of valine betaine was substantially increased during the intervention in Naples ( P  < 0.001) with an inverse correlation with the postprandial insulin concentration. In addition, the concentrations of other betaines, e.g., glycine betaine and proline betaine, correlated with glucose and insulin concentrations at the end of the intervention. Conclusions: Novel betainized compounds in humans are associated with diets rich in whole grains, and they improve insulin resistance and insulin secretion. These results suggest that these novel compounds may contribute to the beneficial effects of whole grain–rich diets. The studies were registered at clinicaltrials.gov as NCT00945854 (Naples) and NCT00573781 (Kuopio).